A new perovskite-related ceramic with colossal permittivity and low dielectric loss. Issue 12 (September 2020) - Peng, Zhanhui; Wang, Jitong; Liang, Pengfei; Zhu, Jie; Zhou, Xiaobin; Chao, Xiaolian; Yang, Zupei
Highlights: For the first time NCBCTO ceramics were designed and prepared via an ordinary mixed-oxide technique. A decent dielectric property with colossal permittivity εr ∼1.5 × 10 4 and low loss tan δ ∼0.04 at 1 kHz were achieved. Electronic heterogeneity structure was clarified, which consist of large resistance insulating grain boundaries and semiconducting grains. Internal barrier layer capacitor effect was adopted to explain the decent dielectric performance. Abstract: We designed a new type of perovskite-related dielectric energy storage material Na1/3 Cd1/3 Bi1/3 Cu3 Ti4 O12 with colossal permittivity via an ordinary solid-state method. Remarkably, the Na1/3 Cd1/3 Bi1/3 Cu3 Ti4 O12 ceramic sintered at 1030 °C displays a decent dielectric performance of colossal permittivity ∼1.5 × 10 4 and low dielectric loss ∼0.04 at 1 kHz. Electric heterogeneity structure in Na1/3 Cd1/3 Bi1/3 Cu3 Ti4 O12 ceramics was clarified, which consists of insulating grain boundaries and semiconducting grains. Notably, internal barrier layer capacitor effect was adopted to explain the decent dielectric performance based on the analysis of dielectric response behavior and complex impedance. Three dielectric anomalies were evidenced in dielectric temperature spectra. Our finding in this work not only explored the dielectric response of the new type of giant dielectric ceramics Na1/3 Cd1/3 Bi1/3 Cu3 Ti4 O12 but also provided candidate materials for high energy storage density capacitors.